Nothing new, it is the same old thing: reflections about black women - Lopes, Maria Aparecida Oliveira (Revista Hipótese, 2016)
This article presents briefly, in light of the literature of the social sciences and historical, reflections regarding the social roles of black women and mestizo as mother, worker, religious and cultural leadership, and enters into the question of citizenship. The text of the common thread is an idea already discussed in the social sciences: face the loneliness by black women. The attempt was to broaden the debate about loneliness to talk with the thought of a US black feminist who finds difficulty to face the loneliness in intellectual work.
Keywords: History; Gender; Black population